Developmental trajectories of adiposity from birth until early adulthood and association with cardiometabolic risk factors - Araújo, J (2015)
Objective: To identify developmental trajectories of adiposity from birth until early adulthood, and to investigate how they relate with cardiometabolic risk factors at 21 years of age. Methods: Participants’ weight and height measurements were obtained using the EPITeen cohort protocol at 13, 17 and 21 years of age, and extracted from child health books as recorded during health routine evaluations since birth. Blood pressure, triglycerides, cholesterol and insulin resistance (HOMA-IR) were assessed at 21 years. Trajectories were defined using 719 participants contributing 11 459 measurements. The individual growth curves were modelled using mixed-effects fractional polynomial, and the trajectories were estimated using normal mixture modelling for model-based clustering. Differences in cardiometabolic risk factors at 21 years according to adiposity trajectories were estimated through analysis of covariance (ANCOVA), and adjusted means are presented. Results: Two trajectories—‘Average body mass index (BMI) growth’ (80.7%) and ‘Higher BMI growth’ (19.3%)—were identified. Compared with those in ‘Average BMI growth’, ‘Higher BMI growth’ participants were more frequently delivered by caesarean section, mothers were younger and had higher BMI, and parental education was lower; and at 21 years showed higher adjusted mean systolic (111.6 vs 108.3 mm Hg, P<0.001) and diastolic blood pressure (71.9 vs 68.4 mm Hg, P<0.001), and lower high-density lipoprotein cholesterol (53.3 vs 57.0 mg dl−1, P=0.001). As there was a significant interaction between trajectories and sex, triglycerides and HOMA-IR were stratified by sex and we found significantly higher triglycerides, in males, and higher HOMA-IR in both sexes in ‘Higher BMI growth’ trajectory. All the differences were attenuated after adjustment for BMI at 21 years. Conclusions: In this long-term follow-up, we were able to identify two adiposity trajectories, statistically related to the BMI and cardiometabolic profile in adulthood. Our results also suggest that the impact of the adiposity trajectory on cardiometabolic profile is mediated by current BMI.